Bankacılık kredi risk ölçümünde aktüeryal modelleme - Tiryaki, Tercan (My University, 2012)
BANKACILIK KREDİ RİSK ÖLÇÜMÜNDE AKTÜERYAL MODELLEME Bankacılık faaliyeti içinde en çok bilinen ve en fazla zarar üretme potansiyeline sahip risk türü, kredi riskidir. Kredi riskinin ölçümü, ulusal ve uluslar arası denetim otoritelerinin son yıllarda finansal sistem istikrarı amacıyla takip ettikleri hususların başında gelmektedir. Bankaların mali yeterlilikleri ve risk ölçümünün objektif, sayısal temele dayanması finansal sistemin istikrarında önemli bir rol oynar hale gelmiştir. Bankaların mali yeterliliğinin değerlendirilmesinde, kredi riskinin ölçümü ve bu risk için ihtiyaç duyulan sermaye tutarı gerek denetim otoritelerinin gerekse banka yönetimlerinin üzerinde durdukları temel hususlardandır. Bu çalışmada kredi risk ölçüm metotlarından aktüeryal modelleme hakkında ayrıntılı bilgi sunulmaya çalışılmış, aktüeryal modellemenin temel unsurları hakkında bilgi verilmesi amaçlanmıştır. Bu çalışmanın amacı, CreditRisk+ modelinde kullanılan aktüeryal yaklaşımla, Türk Bankacılık sektör verilerine uygun aktüeryal bir model uygulamasıdır. Finansal kuruluşlar kredi portföyleri için ihtiyaç duyacakları ekonomik sermaye düzeyini hesaplamak için kredi risk modelleri kullanmaktadır. Beklenen zararlar için karşılık ve rezervler hesaplanırken, beklenmeyen zararlar için ekonomik sermaye hesaplaması yapılmaktadır. Kredi modellerinin temel çıktısı portföy kredi zararlarının ihtimali yoğunluk fonksiyonudur (PDF). Bu hasar (zarar) dağılımından (finansal kuruluşun kredi portföyünden dolayı) beklenen ve beklenmeyen zararlarını tespit etmek mümkün olmaktadır. Beklenen zarar, hasar dağılımının ortalaması olurken, beklenmeyen zarar ise beklenen zarardan “sapmaların” ortalaması olmakta ve portföy riskini ölçmektedir. Bankacılık Kredi Riski Ölçümü, Aktüeryal Modelleme

ACTUARIAL MODELLING IN BANKING CREDIT RISK MEASUREMENT The most obvious risk of a bank by the nature of its activity is credit risk, typically the largest type of risk in terms of potential losses. The measurement of credit risk has recently become a core topic widely discussed by both national and international supervisory authorities pursuing the objective of financial system stability. Since Banks are the most important player in Financial system their health which is able to measured by their solvency is the key importance international level that’s why banks are institutions subject to rigorous supervision and regulation aimed at avoiding that a systemic crisis might affect the general economic system and global economic system. Credit risk measurement is the one of the most important part of banking risk management system. This paper examined actuarial modelling which is the one of the credit risk measurement model, provided detailed information about modelling and its foundations. The goal of this thesis is to applying a model that measures credit risk, by using Turkish Banking sector’s data with actuarial techniques that has been explained in CreditRisk+ model. Financial institutions apply credit risk models to evaluate the “economic capital” necessary to face the risk associated with their credit portfolios. In such a framework, provisions for credit losses should cover expected losses, while economic capital is seen as a cushion for unexpected losses. The main output of a credit risk model is the density function of the portfolio credit loss probability (probability density function – PDF). From the analysis of such loss distribution, a financial institution can estimate both the expected loss and the unexpected loss of its credit portfolio. The expected loss equals the (unconditional) mean of the loss distribution; it represents the amount the bank can expect to loose within a specific period of time (usually one year). On the other side, the unexpected loss represents the average “deviation” from expected loss and measures the actual portfolio risk. Banking Credit Risk Measurement, Actuarial Modelling.
Keywords: Bankalar ve Bankacılık; Risk Yönetimi